2014
DOI: 10.1111/ajsp.12076
|View full text |Cite
|
Sign up to set email alerts
|

Conflict, fear and social identity in Nagaland

Abstract: This survey study tested the effects of exposure to ethnopolitical conflict and violence and social group identification on psychosocial well-being among a sample of Nagas (n = 280). Nagaland is located in Northeast India, and for decades has suffered from armed conflict and political instability. It was predicted that reported exposure to conflict would be positively associated with reported levels of fear, which in turn would decrease psychosocial well-being (assessed with the indices life satisfaction, self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Depressive symptoms were measured with 12 items similar to those used in Zagefka and Jamir (2015; six reversed, 1 = strongly disagree to 7 = strongly agree ). Example items are “Have you recently been able to concentrate on what you were doing?” “Have you recently lost much sleep over worry?” and “Have you recently felt that you are playing a useful part in things?” (reversed), α = .88.…”
Section: Methodsmentioning
confidence: 99%
“…Depressive symptoms were measured with 12 items similar to those used in Zagefka and Jamir (2015; six reversed, 1 = strongly disagree to 7 = strongly agree ). Example items are “Have you recently been able to concentrate on what you were doing?” “Have you recently lost much sleep over worry?” and “Have you recently felt that you are playing a useful part in things?” (reversed), α = .88.…”
Section: Methodsmentioning
confidence: 99%
“…The only noteworthy difference between the results for Studies 1 and 2 was the path from minority identification to stress—this was negative for Muslim women, but non‐significant for Somalis. As we have speculated elsewhere (Zagefka & Jamir, ), whether a minority identity is fit to buffer against stress might depend on the extent to which the identity is imbued with negativity. Of course, African Americans are undoubtedly potential victims of discrimination (Branscombe et al, ).…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, Giamo, Schmitt, and Outten () found that only certain facets of identification (but not others) enhance well‐being. In one of our own studies, we failed to confirm the protective properties of identification for a sample of Naga (Zagefka & Jamir, ). We speculated that this might have been the case because Naga identity is imbued with even more negativity, disadvantage and stigma than African American identity, which the rejection‐identification model originally focussed on.…”
Section: Identification and Acculturation Preferencesmentioning
confidence: 77%
See 1 more Smart Citation
“…A range of other psychological needs can also be fulfilled by being a member of social groups (Capozza et al, 2006;Vignoles et al, 2006). By and large, identification with social groups has consistently been linked to greater well-being in Western settings (Branscombe et al, 1999) and beyond (Zagefka & Jamir, 2015).…”
mentioning
confidence: 99%